The impact of fiscal policy on female labor force participation in Egypt - Emad Attia Mohamed Omran; Yuriy Bilan (Problems and Perspectives in Management, 2023)
There is no doubt that women play a vital role in all aspects of economic activities around the globe. However, despite the great efforts that governments have made over the past three decades to increase women’s integration into the labor market, their participation is still relatively low compared to men. On the other hand, economic literature argues that the government can use fiscal policy tools such as tax revenue and spending to decrease gender inequality in the labor market. The aim of this paper is to investigate the impact of government spending and tax revenue shocks on the female labor force participation rate (the share of women in the total labor force) in Egypt. Annual time-series data were collected from the Central Bank of Egypt and the World Bank from 1990 to 2021, where the vector autoregressive (VAR) model and impulse response functions have been used. The results suggest that government spending and tax revenue shocks increase gross domestic product (GDP) growth rate, female labor force participation, and inflation. Results validated the research hypotheses and showed that a one standard deviation shock to either government spending or tax revenue has a positive impact on female labor force participation. Therefore, the study recommends that using an expansionary fiscal policy may increase the accessibility of Egyptian women to the labor market.